Web based Hostel Management System for Sekolah Menengah Agama Parit Sulong - Anis, Nur'adilah Farhana; Mohd Safar, Noor Zuraidin (Applied Information Technology And Computer Science, 2022)
Hostel Management System is a system which has its’ own database system and a web interface. In today's era of technological advancement, there are hostels that do not have a hostel management system. This database system functions almost same as an application system that able hostel applicants by just fill in the form provided. It then sends the record to the database where hostel management in charge of the hostel can manage the records using a web interface designed to display all the records. This system also can be used by students to check their application and application status records. The three objectives are to design a website system to record hostel applicant application data, to develop a website system to record hostel applicant application data, and to test a website system that record hostel applicant application data. This database system is created using Adobe Dreamweaver 2021. The web system is created using this free hosting service and to develop the web interface. These software and services use because it is among the quality products and easier to learn. This system is expected to help hostel applicants, school admin and hostel management perform their respective roles only through this system without having any meetings during the application process.